Strategic School Leadership in Implementing Character Education for Environmental Awareness: A Case Study in an Indonesian Islamic Primary School - Zainuddin, Zainuddin; Agus R, Abu Hasan (Yayasan Avicenna, 2024)
This study explores the strategic role of school leadership in implementing character education that promotes environmental awareness in a primary Islamic school in Indonesia. Conducted at SD Islam Siti Chodijah, Probolinggo, the research responds to the ongoing gap between formal learning and students’ environmental behavior, which often reflects weak implementation of character-based ecological values. Using a qualitative approach with a phenomenological design, this research investigates the lived experiences and strategies adopted by the principal to instill environmental character values. Key leadership strategies identified include the reinforcement of the school’s vision and mission, periodic teacher training, community and parental involvement, the application of fair reward and sanction systems, and routine monitoring and evaluation. Implementation is carried out through a series of school programs such as SENSE (healthy morning exercises), SIROSA (corridor literacy), WAKABIRRU (time for honoring parents), JUMBERKAH (clean and blessed Fridays), BUSPATA (proper waste disposal), and SERABI, KUKIS, METASEKA, and MEPISEKA—programs designed to cultivate personal and collective hygiene habits. The findings highlight that effective leadership is instrumental in integrating character education with daily school practices, bridging pedagogical vision with actionable programs. This research contributes to the discourse on school-based environmental character education and offers practical insights for education policymakers and practitioners in similar contexts.